2016
DOI: 10.1007/s13277-016-4842-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of growth-4 is a potential target for cancer therapy

Abstract: The inhibitor of growth-4 (ING-4) belongs to the inhibitor of growth (ING) family that is a type II tumor suppressor gene including five members (ING1-5). As a tumor suppressor, ING4 inhibits tumor growth, invasion, and metastasis by multiple signaling pathways. In addition to that, ING4 can facilitate cancer cell sensitivity to chemotherapy and radiotherapy. Although ING4 loss is observed for many types of cancers, increasing evidences show that ING4 can be used for gene therapy. In this review, the recent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“… 8 Moreover, ING4 regulates the NF-κB signaling pathway by modifying gene transcription. 10 , 13 , 37 Therefore, we investigated whether ING4 could enhance the antitumor effect by inhibiting the NF-κB signaling. Consistent with previous reports, our results indicated that infection with oVV-ING4 downregulated the expression of components of the NF-κB family including p52/p100, p65, and p-p65 ( Figure 3B ) and induced apoptosis ( Figure 3A ).…”
Section: Discussionmentioning
confidence: 99%
“… 8 Moreover, ING4 regulates the NF-κB signaling pathway by modifying gene transcription. 10 , 13 , 37 Therefore, we investigated whether ING4 could enhance the antitumor effect by inhibiting the NF-κB signaling. Consistent with previous reports, our results indicated that infection with oVV-ING4 downregulated the expression of components of the NF-κB family including p52/p100, p65, and p-p65 ( Figure 3B ) and induced apoptosis ( Figure 3A ).…”
Section: Discussionmentioning
confidence: 99%
“… 19 At that respect, delivery of ING4 gene via adenoviral vectors into HCC, 20 , 21 lung carcinoma, 22 colorectal cancer, 23 osteosarcoma, 24 hypopharngeal cancer 25 and other modalities human cancers, was found to not only inhibit tumor growth, angiogenesis and invasion, but also regulate cell proliferation and apoptosis and facilitate tumor cell sensitivity to other adjuvant anticancer agents. 19 , 20 , 21 , 22 , 23 , 24 , 25 Nevertheless, most of these previous trials were based on using the traditional replication-deficient adenoviral vector to deliver ING4 gene, and their data were collectively highlighted the importance of combining ING4 gene with additional antitumor gene or chemotherapeutic drugs to achieve more potent antitumor effects than ING4 gene-based monotherapy. 19 , 20 , 21 , 22 , 23 , 24 , 25 By far, the utility and usefulness of ING4 in gene virotherapy strategy is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…7 A previous study reported that ING4 expression is positive in only 82.3% of the ccRCC renal tissues but in all of the normal renal tissues. 7 A previous study reported that ING4 expression is positive in only 82.3% of the ccRCC renal tissues but in all of the normal renal tissues.…”
Section: Discussionmentioning
confidence: 95%
“…6 Besides, the ING proteins also function as type I TSGs as they are found to be involved in DNA replication and repair. 7 In addition, ING4 also elevates the sensitivity to chemotherapy and radiotherapy in cancer cells. 7 In addition, ING4 also elevates the sensitivity to chemotherapy and radiotherapy in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation